Carbon nanofiber with selectively decorated pt both on inner and outer walls as an efficient electrocatalyst for fuel cell applications - Balan, Beena K.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2009)
A novel electrocatalyst, with excellent Pi dispersion oil the inner and outer wall of a carbon nanofiber (CNF) was prepared by a modified polyol process in which both surface tension and polarity characteristics of the medium were properly adjusted to favor solution entry into the tubular region by capillary filling and homogeneous wetting of the inner wall surface by the solvents. The pristine CNF, which possesses an inherently active inner wall surface and inactive outer Wall surface, led to selective Pt deposition along the inner wall, whereas activation of the outer wall with chemical functionalization resulted in excellent dispersion of Pt along both inner and outer walls. Structural and morphological characterizations using high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD) revealed that when Pt could be dispersed along the inner as well as the Outer walls of CNF, the Pt particle size decreased to almost half as compared to the one With Pt decoration only along a single wall of the Substrate material. Further, electrochemical studies using cyclic voltammetry (CV) and rotating disk electrode (RDE) measurements revealed enhanced methanol oxidation and oxygen reduction properties, respectively. The electrochemical active area obtained for the catalyst with both inner and outer wall Pt decoration wits nearly two times higher than that corresponding to the one with only inner wall Pt decoration. Similarly, the rate constant for the oxygen reduction reaction displayed by this sample was four times higher in comparison with the sample prepared by Utilizing only one wall for Pt decoration.

Carbon nanohorn-derived graphene nanotubes as a platinum-free fuel cell cathode - Unni, SreeKuttan M.; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Puthenpediakkal, Hasna; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Current low-temperature fuel cell research mainly focuses on the development of efficient nonprecious electrocatalysts for the reduction of dioxygen molecule due to the reasons like exorbitant cost and scarcity of the current state-of-the-art Pt-based catalysts. As a potential alternative to such costly electrocatalysts, we report here the preparation of an efficient graphene nanotube based oxygen reduction electrocatalyst which has been derived from single walled nanohorns, comprising a thin layer of graphene nanotubes and encapsulated iron oxide nanopartides (FeGNT). FeGNT shows a surface area of 750 m(2)/g, which is the highest ever reported among the metal encapsulated nanotubes. Moreover, the graphene protected iron oxide nanoparticles assist the system to attain efficient distribution of Fe-N-x and quaternary nitrogen based active reaction centers, which provides better activity and stability toward the oxygen reduction reaction (ORR) in acidic as well as alkaline conditions. Single cell performance of a proton exchange membrane fuel cell by using FeGNT as the cathode catalyst delivered a maximum power density of 200 mW cm(-2) with Nafion as the proton exchange membrane at 60 degrees C. The facile synthesis strategy with iron oxide encapsulated graphitic carbon morphology opens up a new horizon of hope toward developing Pt-free fuel cells and metal-air batteries along with its applicability in other energy conversion and storage devices.
Keywords: carbon nanohorns; carbon nanotube; electrocatalyst; fuel cell; oxygen reduction reaction

CoSe2 supported on nitrogen-doped carbon nanohorns as a methanol-tolerant cathode for air-breathing microlaminar flow fuel cells - Unni, SreeKuttan M.; Mora-Hernandez, Juan M.; Kurungot, Sreekumar; Alonso-Vante, Nicolas (Chemelectrochem, 2015)
The synthesis of CoSe2 nanoparticles supported on nitrogendoped carbon nanohorns (CoSe2/NCNH) and the influence of the interaction of the metal centre with the NCNH on the oxygen reduction reaction (ORR) are reported. CoSe2/NCNH shows a 50 mV lower onset overpotential and a 150 mV positive shift in the half-wave potential compared to CoSe2 supported on carbon and carbon nanohorns. This suggests that the intrinsic activity and the density of active reaction centres of CoSe2 are modified by NCNHs. An air-breathing direct meth-anol microlaminar flow fuel cell (mLFFC) is constructed using CoSe2/NCNH as a methanol-tolerant cathode catalyst. A maximum power density of 10.05 mWcm(-2) and a maximum current density of 124.20 mAcm(-2) are achieved with CoSe2/NCNH compared to the non-doped catalyst, CoSe2/C and Pt/C with 5m methanol as the fuel. The improved activity of CoSe2/ NCNH is attributed to the peculiar morphology and the nitrogen doping of the carbon nanohorns. This catalyst could be a suitable alternative to Pt.
Keywords: carbon nanohorns; chalcogenides; fuel cells; oxygen reduction reaction; platinum